PERANCANGAN WEBSITE PENGADUAN MASYARAKAT TANPA IDENTITAS UNTUK MENDUKUNG LAYANAN PUBLIK DI DINAS KOMINFO BANYUWANGI - Amelia Ismatul Hawa; Zaehol Fatah; Lutfiyatul F Anas (CV. Denasya Smart Publisher, 2025)
Public complaints are an important means of improving the quality of public services. However, many people are still reluctant to submit their complaints for fear of their identities being revealed or receiving threats from the reported party. Furthermore, the lack of satisfaction with the follow-up of reports from the administrator also reduces the level of public participation. The existing web-based complaint application does not provide an anonymous feature, making the public feel insecure. This study aims to design a web-based public complaint application with an anonymous feature equipped with a unique code to maintain the privacy of the reporter. This study uses a Waterfall model software development approach that includes stages such as planning, needs analysis, design, implementation, and system testing. The result of this study is a design of an anonymous public complaint information system that can improve the sense of security, effectiveness, and efficiency of public services at the Banyuwangi Regency Communications and Information Service.